Differences in food insecurity between girls and boys: Evidence from Zimbabwe - Craig Gundersen; Yemisi Kuku; Thomas Kelly (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Using data from a 2004 household-based survey of children, we examine differences between boys and girls in self reports of food insecurity in Zimbabwe. Previous studies have taken only the views of the household head into consideration in categorizing the food insecurity status of the household. By so doing, the possibilities of differential experiences of food insecurity by individual household members were ignored. Results show no gender differences in food insecurity for the children surveyed across all three measures of food insecurity utilized in this paper. Probit and ordered probit regressions were also carried out to further investigate if any differences existed after controlling for other factors. While gender still did not matter, there was some evidence that age did, in addition to other household characteristics. In particular, children in wealthier households were less likely to report food insecurity.
Keywords: I32; O15; O55; 330; food insecurity; gender; orphans; HIV/AIDS; poverty; Africa; Zimbabwe